HOMONYMIC ATTITUDE IN THE WORDS IN WHICH THE NAMES OF CLOTHES AND FOOD IN UZBEK FOLK PAREMS ARE INVOLVED - Bukhdu Nurova Yulduz Ubaydullayevna (Western European Studies, 2024)
Ethnolinguistics is a relatively new science, and its subject and scope, as is sometimes the case in new fields of humanities, have not yet been determined, i.e. it remains unclear which elements of reality it studies. In this sense, we can say that ethnolinguistics is a science at the junction. In recent decades, many such borderline fields of knowledge have appeared, the emergence of “sciences at the junction” is a characteristic feature of both the humanities and natural sciences of our time. Ethnolinguistics is a branch of linguistics that studies the spiritual, cultural, and ethnic characteristics of the life of a people and their reflection in language.
Keywords: ethnolinguistics; Ethnos; linguistics; Oil name